Newcastle disease virus infection induces parthanatos in tumor cells via calcium waves. - Yang Qu; Siyuan Wang; Hui Jiang; Ying Liao; Xusheng Qiu; Lei Tan; Cuiping Song; Venugopal Nair; Zengqi Yang; Yingjie Sun; Chan Ding (PLoS Pathogens)
Parthanatos is distinct from caspase-dependent apoptosis in that it does not necessitate the activation of caspase cascades; Instead, it relies on the translocation of Apoptosis-inducing Factor (AIF) from the mitochondria to the nucleus, resulting in nuclear DNA fragmentation. Newcastle Disease Virus (NDV) is an oncolytic virus that selectively targets and kills tumor cells by inducing cell apoptosis. It has been reported that NDV triggers classic apoptosis through the mitochondrial pathway. In this study, we observed that NDV infection induced endoplasmic reticulum stress (ERS), which caused a rapid release of endogenous calcium ions (Ca2+). This cascade of events resulted in mitochondrial depolarization, loss of mitochondrial membrane potential, and structural remodeling of the mitochondria. The overload of Ca2+ also initiated an increase in mitochondrial membrane permeability, facilitating the transfer of AIF to the nucleus to induce apoptosis. Damaged mitochondria produced excessive reactive oxygen species (ROS), which further exacerbated mitochondrial damage and increased mitochondrial membrane permeability, thus promoting additional intracellular Ca2+ accumulation and ultimately triggering an ROS burst. Collectively, these findings indicate that NDV infection promotes excessive calcium accumulation and ROS generation, leading to mitochondrial damage that releases more calcium and ROS, creating a feedback loop that exacerbates AIF-dependent parthanatos. This study not only provides a novel perspective on the oncolytic mechanism of NDV but also highlights new targets for antiviral research.